Risk of Abnormal Uterine Bleeding in Women with Chronic Spontaneous Urticaria: Korean Nationwide Population-Based Cohort - Su Yeon Park; Jee Yeon Kim; Ji-Eun Song (Journal of Clinical Medicine, 2026)
Background: Chronic spontaneous urticaria (CSU) is an immune-mediated disorder driven by mast cell activation, whereas abnormal uterine bleeding (AUB) is a heterogeneous condition with diverse etiologies. Although immune and inflammatory dysregulation has been independently implicated in CSU and certain forms of AUB, the association between CSU and AUB remains unclear. We therefore examined whether CSU was associated with AUB. Methods: We performed a retrospective population-based cohort analysis using data from the Korean National Health Insurance Service. Women newly diagnosed with CSU between 2009 and 2021 were individually matched 1:1 with controls according to age, income, and region of residence. Cox proportional hazards regression and Kaplan–Meier analysis were used to evaluate the risk of AUB. Results: The final cohort comprised 890,010 women with CSU and an equal number of matched controls. The incidence rates of AUB were 12.50 and 10.90 cases per 1000 person–years, respectively, yielding an absolute incidence rate difference of 1.60 cases per 1000 person–years (95% CI, 1.54–1.81). CSU was associated with an increased risk of AUB (aHR, 1.155; 95% CI, 1.142–1.168), and this association persisted among women aged